Impact of Vitamin D Level on Sarcopenia in Elderly People: A Critical Review - Khan, Saniya; Kumar, Sunil; Acharya, Sourya; Wanjari, Anil (Journal of Health and Allied Sciences NU, 2023)
Vitamin D insufficiency is a widespread health issue globally, particularly among the elderly. Vitamin D controls and affects the metabolism and functionality of several human systems, including muscle tissue. The action of vitamin D on muscles has been extensively studied, with evidence indicating that this vitamin can increase the osteogenic differentiation of muscle fibers, hence preserving and enhancing muscular strength and athletic performance. Low hormone levels are more common in older people as a result of poor food intake and decreased skin ultraviolet irradiation. As a result, elderly persons who are deficient in vitamin D may be at risk of developing sarcopenia, a geriatric condition defined by gradual loss of skeletal muscle mass and strength that is frequently accompanied by adverse events such as falls, incapacity hospitalization, and mortality. As a result, these activities are seen to be crucial in illuminating the underlying functional condition of the aged, and functional mobility is employed as a technique for assessing fall risk and frailty. Several randomized controlled studies have been done to explore the efficacy of oral treatment in elderly people to prevent or cure sarcopenia; however, the results are still debatable. We describe the biochemical, clinical, and epidemiological data supporting the idea of a causal relationship between vitamin D insufficiency and a higher likelihood of sarcopenia in elderly adults in this narrative review. The muscular system, the biggest organ in the body, contributing to around 40% of body composition, is vital in exercising and glycogen depletion. Sarcopenia, a steady deterioration in muscle mass and strength, and function in the aged can result in prolonged circumstances, wheelchair confinement, and a reduction in quality of life. Diagnosis and control of muscle wasting are vital for improving health and quality of life in industrialized nations with aging populations. Vitamin D, a fat-soluble vitamin, has gained popularity in recent years because of its relevance in sarcopenia. The role of vitamin D deficiency and fortification on muscle wasting will be the focus of this review.
Keywords: vitamin D; sarcopenia; aging; quality of life